Implementation of Green Economy Through Integrated Urban Farming as Family Economic Resilience During The Pandemic: Maqasid Sharia Perspective - Muhamad Subhi Apriantoro; Indah Noor Rahayuningsih; Sarwanto Sarwanto (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
Due to the corona virus's fall in different economic areas, many individuals have difficulties fulfilling their basic demands. Urban farming is one of the answers to food availability, and their primary concerns are food safety, food pricing, and stimulating the local economy. People cultivated short-lived crops in tiny pots or used the hydroponic method in their yards. Integrated urban farming is a type of green economic activity that adheres to maqasid sharia's maslahah aim. Field research is used to gather essential data. It is conducted on the site to be studied and supplemented with field data in the form of interviews. This study is descriptive, with an emphasis on analysis using a logical method. The green economy with integrated urban farming aims to improve the community's economic well-being and can help mitigate the risk of substantial environmental harm, including the pandemic's detrimental impact on macro and micro food security. It can be observed that the green economy concept can be integrated with the pure maqasid sharia values harmoniously.